Environmental Sanitation and Scabies Incidence among Santri in Islamic Boarding School in Jember Regency - Ali, Khaidar; Rizaldi, Muhammad Addin; Putri, Serius Miliyani Dwi (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2024)
Background: Scabies, caused by the Sarcoptes scabiei mite, remains a significant public health concern, particularly in densely populated environments such as Islamic boarding schools. This study aims to explore the environmental sanitation and the incidence of scabies among santri in Islamic boarding schools in Jember. Methods: This quantitative study employed cross-sectional approach to capture dependent and independent variable at the same time. The dependent variable was scabies incidence, and independent variable was environmental sanitation. The Islamic boarding school was divided and clustered into two group, namely Khalafi (modern) and Salafiyah (Conservative). The data was analyzed by univariately or descriptively. Results: The incidence of scabies among santri in Khalafi and Salafiyah in Jember is 46.07% and 25.81%, respectively. Although the dormitory density is in high category, the sanitation facility in both Khalafi and Salafiyah is low (score <10) with the result of environmental sanitation does not meet requirements. Conclusions: This finding indicates that poor sanitation level was identified in Islamic boarding schools in Jember, where a high scabies incidence was found. Therefore, Health Office of Jember need to establish regular health inspection and initiate the pesantren health post in Islamic boarding school in order to prevent the transmission for the disease. In addition, the religious leader should allocate a budget for the provision of sanitation facilities.